2015
DOI: 10.1039/c5nr03807c
|View full text |Cite
|
Sign up to set email alerts
|

Completely <001> oriented anatase TiO2nanoarrays: topotactic growth and orientation-related efficient photocatalysis

Abstract: A TiO2 film has been facilely grown on a Ti foil via a general and simple acid vapor oxidation (AVO) strategy. Based on detailed characterization by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), we found that the TiO2 film was composed of anatase nanoarrays highly oriented along their <001> direction, resulting in a large exposed {001} top surface on the film. The growth mechanism based on a topotactic transformation was proposed according to a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…Although the top light scattering layer induced low amount of adsorbed dye, light scattering effect of cubic particles was dominating over reduction of adsorbed dye, resulting in an increase in J SC (compares N/C vs N 22 ). In addition, it is known that formation of TiO 2 cubes through TiOF 2 intermediate leads to formation of ˂001˃ oriented anatase‐TiO 2 , in which such phase with dominant {001} surfaces has higher surface energy than other thermodynamically stable facets (e.g., 0.90 J/m 2 for {001} facets, 0.53 J/m 2 for {100} facets, and 0.44 J/m 2 for {101} facets) . Consequently, all double layer devices show higher short circuit current density than N 22 Cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the top light scattering layer induced low amount of adsorbed dye, light scattering effect of cubic particles was dominating over reduction of adsorbed dye, resulting in an increase in J SC (compares N/C vs N 22 ). In addition, it is known that formation of TiO 2 cubes through TiOF 2 intermediate leads to formation of ˂001˃ oriented anatase‐TiO 2 , in which such phase with dominant {001} surfaces has higher surface energy than other thermodynamically stable facets (e.g., 0.90 J/m 2 for {001} facets, 0.53 J/m 2 for {100} facets, and 0.44 J/m 2 for {101} facets) . Consequently, all double layer devices show higher short circuit current density than N 22 Cell.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is known that formation of TiO 2 cubes through TiOF 2 intermediate leads to formation of ˂001˃ oriented anatase-TiO 2 , in which such phase with dominant {001} surfaces has higher surface energy than other thermodynamically stable facets (e.g., 0.90 J/m 2 for {001} facets, 0.53 J/m 2 for {100} facets, and 0.44 J/m 2 for {101} facets). 30,31 Consequently, all double layer devices show higher short circuit current density than N 22 Cell. Keeping in mind Table 4 and Figure 14, it can be observed that N/NC 25 has higher dye loading than N/NC 50 ; however, the latter cell shows higher PCE and J SC than the former cell.…”
Section: Double Layer Dscsmentioning
confidence: 99%
“…Typical methods include fabrication of TiO 2 with morphologies giving short paths of photogenerated charges to the surface, 8 tuning the ratio of polymorphs 9 and control over the exposed crystal facets of TiO 2 . 10 Another method by which recombination may be reduced is the formation of a composite with another photocatalytic material. 11 Choice of material for combination with TiO 2 is key in the success of applying this strategy, as the band energies must align correctly for charges to separate across the interface efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…

We present ar oom temperature topotactic consolidation of cobalt and zinc constituents into monocrystalline CoZn hydroxide nanosheets,b yalocalized corrosion of zinc foils with cobalt precursors.B yv irtue of similar lattice orientation and structure coordination, the hybrid hydroxides amalgamate atomically without phase separation. [2] Nonetheless,o btaining high-quality monocrystalline topochemical reactions is still ac hallenge and often demands high-temperature processes [3] or expensive equipment, such as ultrahigh vacuum pulsed laser, [4] thereby making the technique impractical for largescale applications.F urthermore,r eported topotactic transformations,s uch as metal oxidization, [5] phase transition, [6] and conversion of hydroxides into oxides or metals, [7] primarily involve as ingle metal cation, which precludes formation of bi-/multinary constituents.Inthe context of the ability of multi-component materials to alter electronic states that exhibit strong interplay between the strength of surface intermediate bonds and electrochemical reactivity, [8] it is essential to readily access topotactic consolidation of two or more constituents within ah omogeneous entity.Herein, we demonstrate am ild room temperature topotactic consolidation of cobalt-zinc hydroxides (CZH) with an ensemble of nanosheets,byaninsitu corrosion of zinc foils mediated by cobalt precursors.T he defining advantage of such am etal corrosion technique is its undeniably simple low-cost route,w hich enables spontaneous electrochemical dissolution-redeposition without the expense of external energy.T he chemical etching dissolves metals into their ion derivatives,w hich further self-assemble into their respective oxides or inorganic salts. [1] Thep rowess of topotactical conversion is that it supersedes equilibrium crystal shapes/habits,t hereby allowing phase to be correlated with coordinated structures at atomic homogeneity.

…”
mentioning
confidence: 99%
“…[1] Thep rowess of topotactical conversion is that it supersedes equilibrium crystal shapes/habits,t hereby allowing phase to be correlated with coordinated structures at atomic homogeneity. [2] Nonetheless,o btaining high-quality monocrystalline topochemical reactions is still ac hallenge and often demands high-temperature processes [3] or expensive equipment, such as ultrahigh vacuum pulsed laser, [4] thereby making the technique impractical for largescale applications.F urthermore,r eported topotactic transformations,s uch as metal oxidization, [5] phase transition, [6] and conversion of hydroxides into oxides or metals, [7] primarily involve as ingle metal cation, which precludes formation of bi-/multinary constituents.Inthe context of the ability of multi-component materials to alter electronic states that exhibit strong interplay between the strength of surface intermediate bonds and electrochemical reactivity, [8] it is essential to readily access topotactic consolidation of two or more constituents within ah omogeneous entity.…”
mentioning
confidence: 99%